PENGARUH LATIHAN SQUAT JUMP TERHADAP KEMAMPUAN LOMPAT JAUH SISWA KELAS XI SMAN 1 BAITUSSALAM KABUPATEN ACEH BESAR - fandy irfan irfandi (Sport Pedagogy Journal, 2022)
The purpose study One of the factors behind this study is to improve students' long jump ability by doing squat jump exercises. This study aims to determine the effect of the squat jump exercise on the long jump ability of class XI students of SMA Negeri 1 Baitussalam Aceh Besar. Methods and Materials The approach used in this research is quantitative research. The type of research used is experimental research with a pre-experimental design. The population in this study were 47 students. The sample in this study was only male students, as many as 28 students. Data collection is done by giving tests to students. Data analysis was performed using statistical formulas (t-test). The results showed that the squat jump exercise had an effect on the long jump ability of class XI students of SMA Negeri 1 Baitussalam Aceh Besar, this was evidenced by a statistical test where the t-count value was 4.22 the t-value obtained (t-count) was compared with the t-count value. Conclusion t in the distribution table (t-table). From the t-table at a significant level = 0.05 with degrees of freedom db = N-1 26-1 = 25 one-tailed test, it is known that the t-table value is 1.71. Thus, it can be concluded that the t-count price t-table value (4.22 1.71).